Hemingway on a Bike - Freeze, Eric, 1974- (University of Nebraska Press, 2014)
"A collage-like mash-up of personal anecdote, popular culture, masculinity, sports, and parenting, Hemingway on a Bike takes readers through the many and varied twists and turns of the life and mind of its author, Eric Freeze. Delving into obsessions and experiences, Freeze's essays display a keen intelligence with insights on topics as diverse as Mormonism and foosball, Angry Birds and professional wrestling, superheroes and free birthing, Ernest Hemingway and Star Trek. "Carnecopia" mashes experiences fishing and snorkeling with an exhibit at Monaco's oceanographic museum to comment on how human beings unwittingly enact harm on their environment. "Bolt" explores the author's fascination with sprinting and shares moments in France and the Midwest, where the words "to bolt" sometimes have unforeseen consequences. "Supergirl" plays on the childhood fascination with superheroes juxtaposed with adulthood manifestations of gendered expectations. By turns playful, poignant, celebratory, and searching, Hemingway on a Bike meanders through ruminations on a number of subjects, and these reflections combine to dissect identity, belonging, and migration in an age when borders and boundaries, whatever the type, are continually transgressed and traversed."--